"\\displaystyle\\textsf{If}\\,\\, f(a)=0\\,\\, \\textsf{then}\\,\\, D-a\\,\\,\\textsf{is a factor}\\,\\,\\textsf{of}\\,\\, f(D)\\\\\n\n\\textsf{So, we have}\\,\\,\nf(D) = (D-a)\\phi(D)\\\\\n\n\\begin{aligned}\n\\frac{1}{f(D)}e^{ax} &= \\frac{1}{(D-a)(\\phi(D))}e^{ax}\n\\\\&= \\frac{1}{D-a}\\left(\\frac{1}{\\phi(D)}e^{ax}\\right)\n\\\\&= \\frac{1}{D-a}\\left(\\frac{1}{\\phi(a)}e^{ax}\\right)\n\\\\&= \\frac{1}{\\phi(a)} \\frac{1}{D-a}e^{ax}\n\\\\&= \\frac{1}{\\phi(a)} e^{ax} \\int e^{-ax}\\cdot e^{ax} \\mathrm{d}x\n\\\\&= \\frac{1}{\\phi(a)} e^{ax} \\int \\mathrm{d}x\n\\\\&= \\frac{1}{\\phi(a)} xe^{ax}\n\\end{aligned}\\\\\n\n\\textsf{Differentiating wrt.}\\,\\, D\\\\\nf'(D) = \\phi(D) + (D-a)\\phi'(D)\\\\\n\\implies f'(a) = \\phi(a)\\\\\n\n\\begin{aligned}\n\\therefore \\frac{1}{f(D)}e^{ax} &= \\frac{1}{\\phi(a)} xe^{ax}\n\\\\&= \\frac{1}{f'(a)} xe^{ax}\n\\\\&= x \\frac{1}{f'(a)} e^{ax}\n\\\\&= x \\frac{1}{f'(D)} e^{ax}\n\\end{aligned}\\\\\n\n\\textsf{Replace}\\,\\, D \\,\\, \\textsf{with}\\,\\, D^2\\,\\, \\textsf{and}\\,\\, a \\,\\, \\textsf{with} \\,\\, ia \\\\\n\\frac{1}{f(D^2)}e^{iax} = x \\frac{1}{f'(D^2)} e^{iax}\\\\\n\\frac{1}{f(D^2)}\\left(\\cos(ax) + i\\sin(ax)\\right) = x \\frac{1}{f'(D^2)} \\left(\\cos(ax) + i\\sin(ax)\\right).\\\\\n\\textsf{Setting}\\,\\, D=ia,\\,\\,f(D^2) = f(-a^2) = 0\\\\\n\\textsf{Equating real and imaginary parts, we have}\\\\\ni)\\,\\,\\frac{1}{f(D^2)}\\left(\\sin(ax)\\right) = x \\frac{1}{f'(D^2)} \\left(\\sin(ax)\\right)\\\\\n\\textsf{and}\\\\\nii)\\,\\,\\frac{1}{f(D^2)}\\left(\\cos(ax)\\right) = x \\frac{1}{f'(D^2)} \\left(\\cos(ax)\\right)"
Comments
Leave a comment